Thursday
March 30, 2017

Post a New Question

Posted by on .

sin^4t-cos^4t/sin^2t cos^2t= sec^2t-csc^2t

i have =(sin^2t+cos^2t)(sin^2t+cos^2t)/sin^2tcos^2t
then do i go =(sin^2t+cos^2t)/sin^2tcos^2t

stumped

  • Trig - ,

    LS = (sin^2 t + cos^2 t)(sin^2 t - cos^2 t)/(sin^2 t cos^2 t)
    = 1(sin^2 t - cos^2 t)/(sin^2 t cos^2 t)
    = sin^2 t/(sin^2 t cos^2 t) - cos^2 t/(sin^2 t cos^2 t)
    = 1/cos^2 t - 1/sin^2 t
    = sec^2 t - csc^2 t
    = RS

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question